Non-lithographic wrinkle nanochannels for protein preconcentration - Chung, Seok; Lee, Jeong Hoon; Moon, Myoung-Woon; Han, Jongyoon; Kamm, Roger D. (WILEY-V C H VERLAG GMBH, 2008)
A simple, non-lithographic method to create a nanofluidic channel array that exploits wrinkles is demonstrated. The dimension and position of the wrinkles can be precisely controlled, producing wrinkle nanochannels (WNCs) that range in size from several tens of nanometers to micrometers. The usefulness of the WNCs is demonstrated by preconcentration of a protein, which is shown to vary linearly. Preconcentration levels of more than 100 can be achieved within 10 minutes.
Keywords: DNA; SEPARATION; CHANNELS